2016
DOI: 10.1140/epje/i2016-16078-5
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of chain ends to the surface of a polymer melt: Effect of surface profile versus chain discreteness

Abstract: Silberberg has argued that the surface of a polymer melt behaves like a reflecting boundary on the random-walk statistics of the polymers. Although this is approximately true, independent studies have shown that violations occur due to the finite width of the surface profile and to the discreteness of the polymer molecule, resulting in an excess of chain ends at the surface and a reduction in surface tension inversely proportional to the chain length, N . Using self-consistent field theory (SCFT), we compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 24 publications
3
19
1
Order By: Relevance
“…Furthermore, it reproduces the simple inverse dependence on N n , first observed in the lattice SCFT of Hariharan et al [27]. In a previous study for monodisperse melts [33], we showed that the reduction in surface tension obeys…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Furthermore, it reproduces the simple inverse dependence on N n , first observed in the lattice SCFT of Hariharan et al [27]. In a previous study for monodisperse melts [33], we showed that the reduction in surface tension obeys…”
Section: Discussionsupporting
confidence: 86%
“…5(a) at ξ = 0, which is attributed solely to the discreteness of the chains, is a significant fraction of that for the finite widths typical of an air/polymer surface (i.e., ξ ∼ a [2,7,8]). This suggests that the importance of chain discreteness is comparable to the details of the surface profile [33], but we will demonstrate later that this is not so.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations